Akuntansi Mudharabah - habibillah, Dovi iwan musthofa; Hamdi, Muhammad; Syaddad, Anwar (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2024)
In line with the development of sharia economics, sharia financial institutions in managing their activities are also required to be more optimal in managing and applying the mudharabah accounting concept as an opportunity or opportunity to develop business or investment with capital that they do not have so as to create a concept of mutual benefit between the parties involved. concerned. In order to obtain these benefits, it is necessary to understand in detail the procedures and criteria and mudharabah accounting that are in accordance with the rules that have been established. So, the purpose of the discussion of this article is to examine the concept of mudharabah accounting in Islamic economics. The importance of this discussion topic as a reference for humans, especially Muslims to be able to understand matters relating to mudharabah accounting.